Implementation of an organ space infection prevention bundle reduces the rate of organ space infection after elective colorectal surgery. Issue 2 (3rd May 2021) - Faragher, Ian; Tham, Nicole; Hong, Michael; Guy, Stephen; Yeung, Justin
Abstract : Background: Surgical site infections (SSIs) are morbid and costly complications after elective colorectal surgery. SSI prevention bundles have been shown to reduce SSI in colorectal surgery, but their impact on organ space infections (OSI) is variable. Adoption of an evidence-based practice without an implementation strategy is often unsuccessful. Our aim was to successfully implement an OSI prevention bundle and to achieve a cost-effective reduction in OSI following elective left-sided colorectal operations. Methods: The Translating Research into Practice model was used to implement an OSI prevention bundle in all patients undergoing elective left-sided colorectal resections by a single unit from November 2018 to September 2019. The new components included oral antibiotics with mechanical bowel preparation, when required, and use of impermeable surgical gowns. Other standardised components included alcoholic chlorhexidine skin preparation, glove change after bowel handling prior to wound closure with clean instruments. The primary outcome was OSI. Secondary outcomes included bundle compliance, unintended consequences and total patient costs. Outcomes were compared with all patients undergoing elective left-sided colorectal resections at the same institution in 2017. Results: Elective colorectal resections were performed in 173 patients across two cohorts. The compliance rate with bundle items was 63% for all items and 93% for one omitted item. There was a reduction in OSI from 12.9% (11 of 85) to 3.4% (3 of 88, p<0.05) after implementation of the OSI prevention bundle. The average cost of an OSI was A36 900. The estimated savings for preventing eight OSIs by using the OSI bundle in the second cohort was A295 198. Conclusion: Successful implementation of an OSI prevention bundle was associated with a reduced rate of OSI after elective colorectal surgery. The OSI bundle and its implementation were cost-effective. Further study is required to investigate the sustainability of the OSI prevention bundle.